DEVELOPMEMT ISSUES OF STATE FINANCIAL CONTROL IN UKRAINE - PIKHOTSKA, Maria (Scientific journal «World of Finance», 2023)
Introduction. The issue of building and creating a holistic system of state financial control in Ukraine is very important and relevant today. It is impossible to increase the efficiency and competitiveness of different sectors of the national economic system, to ensure the life of the state, as well as to reduce the level of shadowing of the economy and corruption without their solution.The purpose of the article is to develop the scientific and methodological foundations of the formation of the system of state financial control in Ukraine on improving the efficiency of its functioning in the conditions of modern challenges and threats.Results. The current state of the state financial control system in Ukraine and the prospects of its further development are considered. The results of the control work of the State Audit Service of Ukraine for 2020–2022 are summarized. It is emphasized that effective state financial control is the most important condition for the existence of a strong state and an important factor in its development. The problems that may arise in the process of creating and building a single system of state financial control. Ways to improve the unified system of state financial control are proposed.Conclusions. According to the results of the study, conclusions are formulated on the need to form a holistic system of financial control, determine the vectors of its development, taking into account the principles of interaction between external and internal control bodies, timely identification economic processes, the course of which must be kept under constant control and supervision of the state.